Dampak Sistem Kerja Hybrid, Sistem Reward Dan Produktivitas Kerja Terhadap Kinerja Karyawan (Studi Literatur Pada Perusahaan BUMN) - Alya Della Rosa; Dheo Rimbano; Bella Dwi Sapera; Taura Venusia Ramadhona; Muhammad Ariel Al Fahira; Wayan Singka Damara (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research examines the impact of hybrid work systems, reward systems, and work productivity on employee performance in state-owned companies. Using the systematic literature review (SLR) method, this research analyzed 45 journals published on various academic platforms such as Google Scholar and Publish or Perish. With a qualitative approach and descriptive analysis, this study investigates how the implementation of a hybrid work system that combines work from home and work from office affects employee performance. The research also explores the role of reward systems as a form of reward and motivation, as well as the impact of work productivity in the context of BUMN. The research results show that these three variables have a significant influence on the performance of BUMN employees, with the hybrid work system providing flexibility which has an impact on work balance, the reward system increasing work motivation, and productivity acting as a benchmark for the success of company performance.